Myths and truths about teeth whitening: A review study (Research, Society and Development, 2025)
A literature review was conducted on pre- and post-dental whitening care, focusing on myths and truths associated with the procedure. Introduction. Dental whitening is a widely requested aesthetic procedure, but it is surrounded by doubts about its safety, efficacy, use of activating lights and abrasive products. Objective. The study aimed to gather and analyze scientific evidence to verify myths and present truths about dental whitening care. Methodology. Six articles, out of ten initially selected, demonstrated that light activation techniques (laser, LED, UV) do not provide significant improvements. Abrasive products, such as activated charcoal, remove only superficial pigments, without altering the enamel structure. Strict dietary restrictions, such as the “white diet”, proved to be unnecessary as long as good hygiene practices are maintained. Results and Discussion. It was found that many myths are propagated by means without scientific support. Gaps were identified in the literature on long-term effects and photonic activation, suggesting the need for further investigations. Final considerations. Professional whitening without the use of activators has proven to be effective and safe, although attention should be paid to possible tooth sensitization. It is recommended that further research be carried out to clarify outstanding issues.